Sanitation politics, legacies, and change in urban South Africa - Alex Kihehere Mukiga (Cogent Social Sciences)
This article examines the historical and contemporary contexts of sanitation services in South Africa. Drawing on colonial and apartheid-era policies, the paper shows how segregation and social class have significantly shaped sanitation delivery in the country. Despite post-1994 policy initiatives to expand services to all South Africans and decentralise governance structures, the paper notes that the legacies of colonial planning and politics complicate meaningful sanitary reforms. It argues that to improve sanitation in informal settlements, it is crucial to contextualise the past legacies and consider the current socio-economic and political progress in urban South Africa. The paper concludes by highlighting the need for comprehensive and integrated approaches to sanitation that consider the issue’s complex historical and contemporary contexts.